Chronic disease vulnerability in Ukraine during armed conflict - Moeen Hamid Bukhari; Iftikhar U. Sikder; Iuliia Pavlova; Nancy Fiedler; Ana Lorena Ruano; Ubydul Haque (Communications Medicine, 2026)
Abstract Background Armed conflicts, like the Russian invasion of Ukraine, devastated healthcare systems and amplified chronic disease burdens. This study aimed to unveil links between environmental and social factors and chronic illnesses during crises. Methods This study uniquely combined individual-level data on chronic diseases, living conditions, and winter preparedness in Ukraine during crisis conditions. A multivariable logistic regression model, using age- and gender-adjusted analyses, revealed associations, while machine learning models employed rigorous feature selection and data balancing. Six algorithms predicted disease outcomes using validated metrics, and interpretable insights. Results Surveying 1552 adults during the Russia-Ukraine war, we show that chronic disease prevalence is strongly linked to conflict-driven living conditions. Poor indoor environments disrupted access to medicines, food, transport, and care, and economic shocks consistently were consistently associated with higher disease prevalence/risk. Machine-learning models identified distinct environmental and socioeconomic predictors across hypertension, coronary heart disease, asthma, chronic obstructive pulmonary disease, and arthritis, enabling conflict-specific vulnerability mapping. Conclusion This study reveals links among environment, socioeconomic status, and healthcare access in the context of chronic disease risks during armed conflicts, highlighting the need for targeted policy implementation to improve healthcare accessibility and reduce health disparities.